Murasaki’s Epistemological Awakening: Buddhist Philosophical Roots of The Tale of Genji - Wawrytko, Sandra A. (Journal of Chinese philosophy, 2022)
I approach Murasaki Shikibu’s marvelous literary pearl The Tale of Genji (Genji Monogatari) as analogous to glistening orbs that “come out of the disease of suffering oysters,” the suffering being the death of her beloved husband Fujiwara no Nobutaka (950?–1001). In addition to drawing evidence from the novel itself, I have relied on Murasaki’s lesser-known Poetic Memoirs and Diary that offer important insights into her state of mind and circumspect literary style. The Lotus Sūtra is the key that unlocks Murasaki’s philosophical intent, with its use of parables and poems to provoke deeper understandings of Buddhism and personal realizations. The Buddhist principle of impermanence (Sanskrit anitya; Japanese mujōkan) serves as both the aesthetic of aware and an unavoidable fact that residents of the Heian court (like those in the Lotus Sūtra’s Burning House) choose to ignore or escape by reveling in superficial pursuits of beauty and political power. Various characters in the novel attempt to follow the path to the epistemological awakening the author Murasaki sought for herself.